Peroxisome proliferator-activated receptor-delta agonist ameliorated inflammasome activation in nonalcoholic fatty liver disease - Lee, Hyun Jung; Yeon, Jong Eun; Ko, Eun Jung; Yoon, Eileen L; Suh, Sang Jun; Kang, Keunhee; Kim, Hae Rim; Kang, Seoung Hee; Yoo, Yang Jae; Je, Jihye; Lee, Beom Jae; Kim, Ji Hoon; et al. (World journal of gastroenterology : WJG, 2015)
To evaluate the inflammasome activation and the effect of peroxisome proliferator-activated receptors (PPAR)-δ agonist treatment in nonalcoholic fatty liver disease (NAFLD) models. Male C57BL/6J mice were classified according to control or high fat diet (HFD) with or without PPAR-δ agonist (GW) over period of 12 wk [control, HFD, HFD + lipopolysaccharide (LPS), HFD + LPS + GW group]. HepG2 cells were exposed to palmitic acid (PA) and/or LPS in the absence or presence of GW. HFD caused glucose intolerance and hepatic steatosis. In mice fed an HFD with LPS, caspase-1 and interleukin (IL)-1β in the liver were significantly increased. Treatment with GW ameliorated the steatosis and inhibited overexpression of pro-inflammatory cytokines. In HepG2 cells, PA and LPS treatment markedly increased mRNA of several nucleotide-binding and oligomerization domain-like receptor family members (NLRP3, NLRP6, and NLRP10), caspase-1 and IL-1β. PA and LPS also exaggerated reactive oxygen species production. All of the above effects of PA and LPS were reduced by GW. GW also enhanced the phosphorylation of AMPK-α. PPAR-δ agonist reduces fatty acid-induced inflammation and steatosis by suppressing inflammasome activation. Targeting the inflammasome by the PPAR-δ agonist may have therapeutic implication for NAFLD.